The Role of Amenities and Accessibility on Domestic Tourism Demand in Indonesia - Maya Dethan; Khoirunurrofik Khoirunurrofik (Jurnal Ekonomi Kuantitatif Terapan, 2025)
Tourism sector is one of the key sectors in the national economy. This study aims to analyze the impact of amenities and accessibility on domestic tourism demand in Indonesia using the Fixed Effect Model (FEM) with panel data. The results show that the number of hotels and road quality have a positive and significant effect on the number of domestic tourist trips, while airport and port infrastructure do not significantly influence tourism demand. Additionally, per capita income is identified as a major determinant of domestic travel decisions. It implies that the government should increase in the provision of road infrastructure and support the growth of the hotel sector to stimulate domestic tourism. Tourism industry’s stakeholders should also optimize land-based travel promotions and provide more accommodation options suitable for various tourist segments.